Loss of stromal JUNB does not affect tumor growth and angiogenesis. Issue 6 (9th October 2013) - Braun, Jennifer; Strittmatter, Karin; Nübel, Tobias; Komljenovic, Dorde; Sator‐Schmitt, Melanie; Bäuerle, Tobias; Angel, Peter; Schorpp‐Kistner, Marina
<x xml:space="preserve">Abstract</x> The transcription factor AP‐1 subunit JUNB has been shown to play a pivotal role in angiogenesis. It positively controls angiogenesis by regulating Vegfa as well as the transcriptional regulator Cbfb and its target Mmp13. In line with these findings, it has been demonstrated that tumor cell‐derived JUNB promotes tumor growth and angiogenesis. In contrast to JUNB's function in tumor cells, the role of host‐derived stromal JUNB has not been elucidated so far. Here, we show that ablation of Junb in stromal cells including endothelial cells (ECs), vascular smooth muscle cells (SMCs) and fibroblasts does not affect tumor growth in two different syngeneic mouse models, the B16‐F1 melanoma and the Lewis lung carcinoma model. In‐depth analyses of the tumors revealed that tumor angiogenesis remains unaffected as assessed by measurements of the microvascular density and relative blood volume in the tumor. Furthermore, we could show that the maturation status of the tumor vasculature, analyzed by the SMC marker expression, α‐smooth muscle actin and Desmin, as well as the attachment of pericytes to the endothelium, is not changed upon ablation of Junb. Taken together, these results indicate that the pro‐angiogenic functions of stromal JUNB are well compensated with regard to tumor angiogenesis and tumor growth.